Profile of Paediatric Malignancies: A Five Year Study - Jabeen, S; Haque, M; Islam, MJ; Talukder, MH (Journal of Dhaka Medical College, 2010)
Objective: The objective of this study was to find out the profile of childhood cancers in National Institute of Cancer Research and Hospital, (NICRH), Dhaka during 2005 to 2009. Methodology: It was a retrospective study using hospital based cancer registry records from January 2005 to December 2009. All the children below 15 years with confirmed diagnosis of cancer by means of histological or cytological examinations were included in this study. Results: There were 28409 new confirmed cases attended out patient department of NICRH during these 5 years. Among which 1250 were below 15 years of age. An average 250 cases attended per year. Overall pediatric tumours were 4.4% of total cancers. The frequency of cancer was found to be higher among boys (62%) than girls (38%) with a ratio of 1.6:1. Majority of the children were from rural areas (67%) compared to (33%) from urban areas. The results showed that Lymphoma (24.2%), Retinoblastoma (17.4%) and Leukaemia (14.3%) were the commonly found childhood cancers among the children attended at NICRH during data collection period. Other less commonly found tumor were bone tumour (7.2%), kidney tumor (6.8%) Central Nervous System Tumour (3.7%),Testicular Tumour (3.7%), and Hepatocellular cancer (1.3%). Conclusion: Lymphoma, acute lymphoblastic leukemia and bone tumor commonly found in children above 5 years in contradiction to retinoblastoma, leukaemia and lymphoma which were prevalent in children less than 5 years of age. Key Words: Cancer registry; paediatric malignancies; cancer profile. DOI: 10.3329/jdmc.v19i1.6249 J Dhaka Med Coll. 2010; 19(1) : 33-38.